KARAKTERISTIK ARANG AKTIF DARI TUNGGAK Acacia crassicarpa - Yeni Aprianis (BRIN Publishing, 2012)
Stump wastes of the felled tree Acacia crassicarpa are not yet used although they are available in large quantity. Converting the stump into actived charcoal maybe one of the most possible uses of the treestump. This experiment investigates the properties of actived charcoal made from Acacia crassicarpa treestump. The treestump was carbonized into charesal, then activated by immersing in H,PO, solution with concentration of 5% and 10% for 90 minutes. The treated charcoal was then beated in retort at various temperatures of 650C, 750°C and 850C. The result showed that good quality of activated charcoal was obtained by using 10% H,PO, at temperature 750 C. The yield of the activated charcoal at this condition was 57%, water content 0,49%, volatile matter 7,37%, ash content 4,22%, fixed carbon 88,41%, adsorptive capacity of indine 1115,5 mg/g, adsorptive capacity of benzene 25,52%, adsorptive capacity of cloroform 41,29% and adsorptive capacity of formaldebyde 45,91%. These characteristics met the SNI requirements and the charenal can be used for water purification. It can increase pH of water from 5,63 to 6,9 and reduce metals Fe and Zn respectively from 0,600 and 0,037 mg/L. into 0,424 and 0,024 mg/1. The structure of charcoal is more reguler after activation.